2012
DOI: 10.1111/j.1745-4565.2012.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE OF VIBRIO SPP. IN LOBSTER AND CRAB FROM THE PERSIAN GULF

Abstract: A total of 132 samples, including 100 lobsters and the 32 crab samples, were studied. A biochemical protocol was applied for the identification of the Vibrio isolates. Polymerase chain reaction (PCR) was used to confirm the isolated strains and to detect the tdh and trh genes of Vibrio parahaemolyticus. Vibrio spp. were detected in 25% of the samples analyzed in this study. Among the Vibrio isolates, Vibrio vulnificus was the species most frequently detected (13.6%), followed by Vibrio alginolyticus (9.09%), V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
3
25
1
4
Order By: Relevance
“…Raissy et al . () did not detect the presence of V. parahaemolyticus trh + in lobsters or crab. Only 10% of crab, 20% of haemolymph, 11% of sediment and 2% of water samples were positive for both tdh + and trh + V. parahaemolyticus .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Raissy et al . () did not detect the presence of V. parahaemolyticus trh + in lobsters or crab. Only 10% of crab, 20% of haemolymph, 11% of sediment and 2% of water samples were positive for both tdh + and trh + V. parahaemolyticus .…”
Section: Discussionmentioning
confidence: 80%
“…Our results are consistent with the results of previous studies which reported low incidence of tdh + and trh + V. parhaemolyticus in crabs, sediment and seawater (Duan and Su ; Raissy et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the infectious diseases the luminescent disease causing Vibrio harveyi is one of the most important bacterial pathogen, capable of causing higher mortality among the marine invertebrates (Vezzulli et al, 2010). In the last two decades, mass mortalities (80-100%) among Penaeid shrimps resulting from V. harveyi infections were frequently reported in hatcheries (Raissy et al, 2011) and grow-out ponds (Zhou et al, 2012). V. harveyi has been established as well-known bacterium to produce extra cellular products indicating its virulence factors such as luminescence, proteases, phospholipases, lipases, siderophores, chitinases and hemolysins (Soto-Rodriguez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Vibrio includes gram-negative, facultative anaerobic, non-spore-forming bacilli that are oxidase positive and halophilic 1) . Several species of Vibrio can cause foodborne infection, usually associated with eating undercooked seafood 2) .…”
mentioning
confidence: 99%